THE INDEPENDENT CURRICULUM IN EDUCATIONAL THEORY REVIEW: CHALLENGES AND SOLUTIONS - Mustakim, Mustakim; Suastra, I Wayan; Lasmawan, I Wayan (Universitas Pendidikan Mandalika, 2024)
This research aims to: 1) Analyze the understanding and implementation of the concepts and basic principles of the Independent Curriculum within the context of existing educational theories; 2) Identify the main challenges in educational theory related to the implementation of the Independent Curriculum at the elementary education level; and 3) Evaluate and formulate proposed solutions in educational theory to address the challenges of implementing the Independent Curriculum at the elementary education level. This study employs literature research and case study methods to evaluate the implementation of the Independent Curriculum. The literature research design includes source identification, critical analysis, synthesis of findings, and conclusion drawing. The case study design involves selecting four public elementary schools in the village of Sukarara, data collection through interviews, classroom observations, and document analysis. The results indicate that: 1) Educators have a good understanding of the Independent Curriculum as a flexible curriculum that integrates local wisdom and encourages active student engagement. However, field implementation reveals a gap between theoretical understanding and practice, caused by limited training and resources; 2) The main challenges identified include teacher readiness, availability of educational resources, and administrative support. Many teachers feel unprepared to adopt more innovative and flexible teaching approaches. Additionally, limited resources such as teaching materials and technology pose significant barriers, especially in remote areas. Insufficient policy and administrative support at schools also act as impediments; and 3) Proposed solutions to address these challenges include ongoing professional training and development for teachers, provision of adequate educational resources, and flexible policy support. Enhancing community and parental involvement in the educational process is also considered important for creating a more inclusive and supportive learning environment. The implications of these findings are expected to provide guidance for policymakers and educational practitioners in effectively implementing the Independent Curriculum at the elementary education level.